A converse theorem for Jacobi cusp forms of degree two - Kohnen, Winfried; Martin, Yves; Shankhadhar, Karam Deo (Acta arithmetica, 2019)
We establish a converse theorem for Jacobi cusp forms of degree two. The methods combine and generalize arguments given in works of Imai, Arakawa-Makino-Sato and Martin to a vectorial setting, and they are presented in a detailed manner. As an application
Gesehen am 14.08.2019